Role of HOXC10 in Cancer - Fang, Jinyong; Wang, Jianjun; Yu, Liangliang; Xu, Wenxia (Frontiers in Oncology, 2021)
The HOXC10 gene, a member of the HOX genes family, plays crucial roles in mammalian physiological processes, such as limb morphological development, limb regeneration, and lumbar motor neuron differentiation. HOXC10 is also associated with angiogenesis, fat metabolism, and sex regulation. Additional evidence suggests that HOXC10 dysregulation is closely associated with various tumors. HOXC10 is an important transcription factor that can activate several oncogenic pathways by regulating various target molecules such as ERK, AKT, p65, and epithelial mesenchymal transition-related genes. HOXC10 also induces drug resistance in cancers by promoting the DNA repair pathway. In this review, we summarize HOXC10 gene structure and expression as well as the role of HOXC10 in different human cancer processes. This review will provide insight into the status of HOXC10 research and help identify novel targets for cancer therapy.